Recursive identification and parameter estimation - Chen, Hanfu; Zhao, Wenxiao (CRC Press, Taylor & Francis Group, 2014)
Recursive Identification and Parameter Estimation describes a recursive approach to solving system identification and parameter estimation problems arising from diverse areas. Supplying rigorous theoretical analysis, it presents the material and proposed algorithms in a manner that makes it easy to understand-providing readers with the modeling and identification skills required for successful theoretical research and effective application.